Factors Related to The Event Anemia in Pregnant Women Who Visit at the Andalas Health Center Makassar City - Hilmiah, Hilmiah; Qamarya, Nurul; Masdarwati, Masdarwati; Akib, Asridawati; Kadir, Erni; Rukinah, Rukinah; Rahmat, Rezqiqah Aulia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Anemia is a term that indicates low red blood cell and hematocrit levels below normal values. Anemia is not a disease but a reflection of a disease or impaired body function. Physiologically, anemia occurs when there is a lack of hemoglobin to transport oxygen to all body tissues. In this study, researchers used an analytical descriptive research design that aims to determine the relationship between the level of knowledge, nutritional status, and socioeconomic level with the incidence of anemia at Puskesmas Andalas Makassar city. The approach used in this research is Cross Sectional by making measurements / observations at the same time. The place of this research was carried out at the Andalas Health Center of Makassar City. Based on the results of research conducted on October 12 to November 30, 2015 at Puskesmas Andalas Makassar City, the results of statistical tests using the chi-Square test are p = 0.001 with a level of significance α = 0.05 which means p < 0.05 then ha is accepted and ho is rejected, thus there is a relationship between the level of understanding, the economy of pregnant women with anemia during pregnancy at Puskesmas Andalas Makassar City. So it can be concluded that the relationship between the level of understanding of pregnant women, the relationship between the nutritional status of pregnant women, the relationship between the economy of pregnant women about anemia at Puskesmas Andalas Makassar City exists.